Channels of Labour Supply Responses of Lone Parents to Changed Work Incentives - Xiaodong Gong; Robert Breunig (Institute for the Study of Labor (IZA), 2013)
In this paper, we investigate the response of female lone parents to two reforms to the welfare system in Australia. We look at changes to both hours and participation and focus on the channels of adjustment, in particular the role of job changes for adjustment in hours. We highlight the relationship between policy design and heterogeneous outcomes. Workers/non-workers and mothers with high/low education respond differently to different policies. We find evidence of within job rigidities as the adjustment of working hours happens primarily through changing jobs. Our findings also provide support for the importance of accounting for fixed costs of working.
Keywords: C23; H31; I38; J13; J22; 330; channel of labour supply adjustment; lone mothers; job changes; difference-in-differences